A case study : survey on road safety in jalan hospital, Kangar, Perlis - Nur Syazwana Amira Malihan (School of Environmental Engineering, University Malaysia Perlis, 2016)
A questionnaire survey on road safety was conducted in the state of Perlis where more focus on the road that have been studied, namely Jalan Hospital, Kangar, Perlis. This is because the road is one way to get high in the statistics of road accidents in the state of Perlis. Therefore, to get information about road safety in the region and a study has been done it is to realize its goal of road safety on the roads around it so in a systematic and orderly manner in accordance with the guiding principles that have set by the Public Works Department (PWD). In addition, the contributing factors that can be identified through the investigation reported by accidents have occurred where the parties involved are the driver, the walk and the road environment at the same time it can be obtained through this study the relationship between road users and researchers. Based on this information, the investigation of road user attitude towards speed limits and speeding in general, and to try and understand some of the basic factors behind this attitude. The types of questions in this section is a Likert Scale questions. To facilitate the work of analyzing the data in this study, data were analyzed using two methods, which uses IBM SPSS Statistics 21 software and the Relative Importance Index. In conclusion, all the information can be easily obtained by an inquiry through the fieldwork and questionnaire survey about safety and the factors contributing to road accidents and through this study can also help authorities to further improve road safety in the region.